Diseases affecting the coffee crop: Elucidating the life cycle of Rust, Thread Blight and Cercospora Leaf Spot - Moreira-Morrillo, Anthony A. (2023)
Coffee (Coffea spp.) is the second most significant commodity worldwide, with C. arabica being its most representative species. The coffee crop is affected by different fungal diseases that reduce the photosynthetically active area of its leaves and the production of grains. In order of agronomic importance, the rust caused by the biotrophic pathogen Hemileia vastatrix is a disease difficult to manage due to its type of reproduction. Another no less important, Thread Blight, caused by the basidiomycetes Ceratobasidium noxium (Syn. Corticium koleroga) and C. chavesanum, affects all aerial tissues of plants. The third disease, Cercospora leaf spot caused by Cercospora coffeicola, affects both leaves and grains, making it difficult to manage. Although there is enough scientific information on Rust, very little is known about the etiology, symptomatology, life cycle, and management of Thread Blight and Cercospora leaf spot. High-resolution photographs and micrographs were used and related with available scientific information. In addition, current scientific information on each disease was compiled, and with that, the life cycles were developed. Likewise, this manuscript describes the management of the three diseases based mainly on the use of genetic, cultural, physical, biological, and chemical measures and their integration as a sustainable alternative in the coffee agroecosystem. Current and future challenges in coffee include the evaluation of cultivars, genetic diversity of Ceratobasidium spp. and C. coffeicola, plant-pathogen interactions, and agroecological management practices.